Bio-responsive hydrogels for an in vitro brain cancer cell model: self-controlled inhibition of matrix metalloproteinase activity - Russo, Emanuele (2020)
In nature, an unbalanced level of enzyme activity (e.g. proteases) is correlated to various disease states, particularly cancer. Among them, several studies have established that medulloblastoma (MB), a brain cancer in children, is associated with an overexpression of matrix metalloproteases (MMPs) (predominantly MMP-2), which is the consequence of the downregulation of their natural inhibitors tissue inhibitors of matrix metalloproteases (TIMPs) (e.g. TIMP-2). Although MMP inhibition remains a relevant therapeutic approach, MMP synthetic inhibitors have not converted to clinical application due to their dose-limiting side effects following systemic administration. As a result, the controlled delivery of endogenous MMP inhibitors directly in situ, could therefore provide the re-establishment of the MMP/TIMP equilibrium. The main goal of this work is to develop a MMP-2 responsive hydrogel that could provide an on-demand controlled release of the recombinant tissue inhibitor of MMP-2 (rTIMP-2) in response to elevated MMP-2 activity. This could be beneficial to restore the enzyme/inhibitor equilibrium and provide reduction of tumour growth and metastasis. MMP-2 responsive hydrogels were fabricated through thiol-ene step-growth polymerization of multiarm PEG-norbornene (PEG4-NB) with a MMP-2 recognised peptide sequence. Hydrogels demonstrated their MMP-2 sensitivity through the release of an encapsulated fluorescent dextran probe, as crosslinks are degraded by the enzyme. Following mesh size optimisation using a model dithiothreitol (DTT) cross-linked PEG4-NB hydrogel, MMP-2 responsive hydrogels were found to proficiently encapsulate and retain rTIMP-2, a necessary condition to maintain an exclusively enzyme triggered release. rTIMP-2 loaded hydrogels demonstrated their ability to efficiently inhibit different levels of MMP-2 and to modulate enzyme activity on the basis of the different rTIMP-2 payloads. These outcomes were obtained by monitoring both the residual MMP-2 activity and the subsequent release of a co-encapsulated fluorescent dextran upon MMP-2 action. Lastly, in a preliminary study, rTIMP-2 containing hydrogels proved to be cell biocompatible and able to inhibit MMP-2 secreted by MB cells. These findings promote the potential ability of this bio-responsive hydrogel to promote the renewal of the imbalance between MMP-2 and TIMP-2, an essential condition to reduce medulloblastoma growth.